Virtual and Augmented Reality (VR/AR) Foundations and Methods of Extended Realities (XR) - Doerner, Ralf.; Broll, Wolfgang; Grimm, Paul.; Jung, Bernhard (Cham : Springer International Publishing : Imprint: Springer, 2022)
This comprehensive textbook offers a scientifically sound and at the same time practical introduction to Virtual and Augmented Reality (VR/AR). Readers will gain the theoretical foundation needed to design, implement or enhance VR/AR systems, evaluate and improve user interfaces and applications using VR/AR methods, assess and enrich user experiences, and develop a deeper understanding of how to apply VR/AR techniques. Whether utilizing the book for a principal course of study or reference reading, students of computer science, education, media, natural sciences, engineering and other subject areas can benefit from its in-depth content and vivid explanation. The modular structure allows selective sequencing of topics to the requirements of each teaching unit and provides an easy-to-use format from which to choose specific themes for individual self-study. Instructors are provided with extensive materials for creating courses as well as a foundational text upon which to build their advanced topics. The book enables users from both research and industry to deal with the subject in detail so they can properly assess the extent and benefits of VR/AR deployment and determine required resources. Technology enthusiasts and professionals can learn about the current status quo in the field of VR/AR and interested newcomers can gain insight into this fascinating world. Grounded on a solid scientific foundation, this textbook, addresses topics such as perceptual aspects of VR/AR, input and output devices including tracking, interactions in virtual worlds, real-time aspects of VR/AR systems and the authoring of VR/AR applications in addition to providing a broad collection of case studies.
1 R. Doerner et al., Introduction to Virtual and Augmented Reality -- 2 R. Doerner and F. Steinicke, Perceptual Aspects of VR -- 3 B. Jung and A. Vitzhum, Virtual Worlds -- 4 P. Grimm at al., VR/AR Input Devices and Tracking -- 5 W. Broll et al., VR/AR Output Devices -- 6 R. Doerner et al., Interaction in Virtual Worlds -- 7 M. Buhr et al., Real-time Aspects of VR Systems -- 8 W. Broll, Augmented Reality -- 9 R. Doerner et al., VR/AR Case Studies -- 10 W. Broll et al., Authoring of VR/AR Applications -- 11 R. Doerner, Mathematical Foundations of VR/AR.
Keywords: Image processing-Digital techniques; Computer vision; User interfaces (Computer systems).; Human-computer interaction; Signal processing; Computer Imaging, Vision, Pattern Recognition and Graphics; User Interfaces and Human Computer Interaction; Digital and Analog Signal Processing